2–√2\sqrt 2 + 3" role="presentation">3–√3\sqrt 3 and y = 1 + 2" role="presentation">2–√2\sqrt 2 - 3," role="presentation">3–√,3,\sqrt 3 {\text{,}} then the value of x2+4xy+y2x+y" role="presentation">x2+4xy+y2x+yx2+4xy+y2x+y\frac{{{x^2} + 4xy + {y^2}}}{{x + y}} is?" /> 2–√2\sqrt 2 + 3" role="presentation">3–√3\sqrt 3 and y = 1 + 2" role="presentation">2–√2\sqrt 2 - 3," role="presentation">3–√,3,\sqrt 3 {\text{,}} then the value of x2+4xy+y2x+y" role="presentation">x2+4xy+y2x+yx2+4xy+y2x+y\frac{{{x^2} + 4xy + {y^2}}}{{x + y}} is?" /> 2–√2\sqrt 2 + 3" role="presentation">3–√3\sqrt 3 and y = 1 + 2" role="presentation">2–√2\sqrt 2 - 3," role="presentation">3–√,3,\sqrt 3 {\text{,}} then the value of x2+4xy+y2x+y" role="presentation">x2+4xy+y2x+yx2+4xy+y2x+y\frac{{{x^2} + 4xy + {y^2}}}{{x + y}} is?" />
Post your Comments